2010
DOI: 10.1038/cdd.2010.147
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling-nanotube development in astrocytes depends on p53 activation

Abstract: Tunneling nanotubes (TNTs) can be induced in rat hippocampal astrocytes and neurons with H 2 O 2 or serum depletion. Major cytoskeletal component of TNTs is F-actin. TNTs transfer endoplasmic reticulum, mitochondria, Golgi, endosome and intracellular as well as extracellular amyloid b. TNT development is a property of cells under stress. When two populations of cells are co-cultured, it is the stressed cells that always develop TNTs toward the unstressed cells. p53 is crucial for TNT development. When p53 func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
394
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(432 citation statements)
references
References 37 publications
21
394
1
6
Order By: Relevance
“…The M-Sec-Ral-exocyst pathway seems activated by both p53 and the p53-induced Akt-PI3K-mTOR cascade. Furthermore, hydrogen peroxide changed membrane and cytoskeleton properties and increased TNT connections in astrocytes [110] and induced TNT in hippocampal astrocytes and neurons [74]. Taken together, TNT development in cells appears to take place particularly under stress and may be one way to transfer cellular substances from stressed cells to healthy cells which may increase their stress resistance.…”
Section: (B) Astrocytesmentioning
confidence: 97%
See 2 more Smart Citations
“…The M-Sec-Ral-exocyst pathway seems activated by both p53 and the p53-induced Akt-PI3K-mTOR cascade. Furthermore, hydrogen peroxide changed membrane and cytoskeleton properties and increased TNT connections in astrocytes [110] and induced TNT in hippocampal astrocytes and neurons [74]. Taken together, TNT development in cells appears to take place particularly under stress and may be one way to transfer cellular substances from stressed cells to healthy cells which may increase their stress resistance.…”
Section: (B) Astrocytesmentioning
confidence: 97%
“…However, in astrocytes, it was found that the TNT formation is dependent on p53 activation, a tumour suppressor protein giving cellular and genomic stability [74]. When p53 function is deleted by either dominant negative constructs or siRNAs, TNT development is inhibited.…”
Section: (B) Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this finding is that as early endosomes and the ERC are involved in recycling of proteins between the intracellular environment and plasma membrane, their functions and position might make them more accessible to entering the membrane protrusions caused by TNT formation. However it should be noted that both the ER and Golgi have been reported inside TNT-like structures in cells of different origin 15,16 therefore this could be also cell type specific.…”
Section: Organelles Of the Recycling Pathway Enter Tntsmentioning
confidence: 99%
“…[1][2][3] Recently, it was reported that TNT formation in primary rat hippocampal astrocytes and neurons was dependent on the activation of tumor suppressor protein p53 through cellular stress induction such as hydrogen peroxide (H 2 O 2 ). 4 Considering the broad effect of p53 on numerous cellular functions, 5 we here investigated whether p53 is a key protein needed for TNT formation. We first examined the effect of p53 activation on TNT formation in PC12 and OCI-AML3 (acute myeloid leukemia) cells that express wild-type p53 (p53WT).…”
mentioning
confidence: 99%